The sexuality experience of stoma patients: a meta-ethnography of qualitative research - Siting Lin; Guo Yin; Linghui Chen (BMC, 2023)
Abstract Background As the quality of life of stoma patients has become a research hotspot, sexual health as an integral part of patients' lives has received more and more attention. However, there is a lack of comprehensive reviews on the sexual experiences of patients with stomas. This study aims to synthesize the qualitative literature on the subjective experience of stoma patients' sexual life, to identify their sexual needs, and to provide evidence for the content and methods of sexual health interventions for healthcare professionals. Methods PubMed, Embase, Web of Science, CINAHL, and Scopus were searched for qualitative studies on the sexual experience of stoma patients (from the inception to January 2023). Titles, abstracts, and full texts were reviewed by two researchers. We used the Critical Appraisal Program (CASP) checklist to assess the quality of included articles. Results A total of 1388 articles were retrieved, and eight studies were included. Data was extracted, including three main themes: 1) sexual problems due to changes in physical function and psychological disorders; 2) the relationship with spouse changes; 3) the cognition of sexual life and the need for sexual knowledge. Conclusion Healthcare professionals should pay attention to the sexual life status and sexual health needs of stoma patients and their partners, and give professional guidance and support in treatment and nursing to improve the quality of sexual life of stoma patients.